2006
DOI: 10.1007/s00410-006-0108-1
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Pb paradoxes: the sulfide solution

Abstract: There is growing evidence that the budget of Pb in mantle peridotites is largely contained in sulfide, and that Pb partitions strongly into sulfide relative to silicate melt. In addition, there is evidence to suggest that diffusion rates of Pb in sulfide (solid or melt) are very fast. Given the possibility that sulfide melt 'wets' sub-solidus mantle silicates, and has very low viscosity, the implications for Pb behavior during mantle melting are profound. There is only sparse experimental data relating to Pb p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 87 publications
(104 reference statements)
3
108
1
7
Order By: Relevance
“…The Ce/Pb ratio in the spidergram ($12; Table 3) is approximately half the canonical ratio in OIBs ($25) [Hofmann et al, 1986]. Because it is chalcophile, Pb can be strongly influenced by the presence of sulfides in the mantle source, and as a result the Ce/Pb ratio of the mantle source of high 3 He/ 4 He OIBs (here argued to be $12) may differ from the melt ($25) [Hart and Gaetani, 2006].…”
Section: Estimating Thementioning
confidence: 94%
“…The Ce/Pb ratio in the spidergram ($12; Table 3) is approximately half the canonical ratio in OIBs ($25) [Hofmann et al, 1986]. Because it is chalcophile, Pb can be strongly influenced by the presence of sulfides in the mantle source, and as a result the Ce/Pb ratio of the mantle source of high 3 He/ 4 He OIBs (here argued to be $12) may differ from the melt ($25) [Hart and Gaetani, 2006].…”
Section: Estimating Thementioning
confidence: 94%
“…By contrast, the mantle endmembers Workman et al, 2004;Jackson et al, 2007b) and DMM exhibit spidergrams (Hart and Gaetani, 2006) that lack such pronounced TITAN anomalies (Fig. 1).…”
Section: New Data and Observationsmentioning
confidence: 98%
“…Recent interest in the Pb elemental and isotopic composition of mantle sulfides stems from a potential solution to the first Pb paradox (i.e., the position of oceanic Pb isotopic compositions in the "future" Pb position, to the right of the geochron; Allègre 1969), as discussed in the final section of this chapter. A quantitative Pb mass balance (elemental and isotopic) based upon individual peridotites has yet to be accomplished, despite studies that have suggested that mantle Pb resides predominantly in BMS (Meijer et al 1990;Hart and Gaetani 2006). Hart and Gaetani (2006) predicted that if BMS are the main mantle Pb reservoir they should represent c. 0.05% of the mantle to be consistent with PUM sulfur concentration estimates (Lorand 1990;O'Neill 1991;Palme and O'Neill 2003) and contain ca.…”
Section: Lead Mass Balancementioning
confidence: 99%